(a+2)*(a+3)=3

Simple and best practice solution for (a+2)*(a+3)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+2)*(a+3)=3 equation:



(a+2)(a+3)=3
We move all terms to the left:
(a+2)(a+3)-(3)=0
We multiply parentheses ..
(+a^2+3a+2a+6)-3=0
We get rid of parentheses
a^2+3a+2a+6-3=0
We add all the numbers together, and all the variables
a^2+5a+3=0
a = 1; b = 5; c = +3;
Δ = b2-4ac
Δ = 52-4·1·3
Δ = 13
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-\sqrt{13}}{2*1}=\frac{-5-\sqrt{13}}{2} $
$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+\sqrt{13}}{2*1}=\frac{-5+\sqrt{13}}{2} $

You can always share this solution

See similar equations:

| -6=(5x-12)/3 | | 2a+1=10 | | (2x-1)(x+17)=0 | | 1+7p+p=1 | | 3(m+5)=12 | | 10(z+1)-5(z-2)=2(z-2)+2(z-1) | | (4a-1)=-23- | | 2(m-1)=-5(4m-m) | | -6w-14=8(w-7) | | 3(2x-3)-3=3(x-2)+9 | | X-0,15x=4800 | | (x-10)=-99 | | 1.5=1.2y=5.7 | | 2=10-3(x+7)+5(1-x)+6x | | X=7x-23 | | 4b÷8=20b= | | 4b÷8=20 | | 4.7x+2-4x=7+2x+4 | | 3-x/3=9/2 | | n+22=72 | | 8w?12=?5 | | (10x+9)=(4x+1) | | x^2?7x+2=0 | | 11x5=8x-6 | | 5(3m-2)-9(5-2m)=4m+2(5m+1) | | 2x2=300 | | 5(3m-2)-9(5-2m)=4m+2(5m+1 | | 3x+4=5-9 | | 9/x=98/7 | | 3x+17=32;3 | | 5x+3=15x+7 | | 261=152-v |

Equations solver categories